The glucose crossover concept is not an important new concept in exercise metabolism - Coggan, A. R. (Clinical and Experimental Pharmacology and Physiology, 1997)
1. The basic premise of the 'crossover' concept (i.e. that the balance of carbohydrate (CHO) and fat utilization during exercise depends on the interaction between exercise intensity and the individual's endurance training status) has been accepted since at least the 1930s. 2. The crossover concept differs from earlier perspectives mostly in its greater emphasis on the absolute exercise intensity as an important determinant of substrate selection during exercise. Because of this emphasis, it is argued that while trained subjects may utilize less CHO than their untrained counterparts during low- or moderate-intensity exercise, this is not true during high-intensity exercise, because during such exercise even trained persons must 'crossover' to CHO dependency. In fact, the crossover concept predicts that utilization of at least one CHO source (i.e. plasma-borne glucose) should be greater in trained subjects during intense exercise. This increase in glucose utilization is hypothesized to be supported by an enhanced rate of gluconeogenesis. 3. In direct contradiction of the crossover concept, the literature consistently shows that, compared with untrained individuals, trained subjects rely less on CHO for fuel, even during high-intensity exercise. In particular, it has been shown that the rate of glucose utilization is lower in trained subjects under these conditions. Recent data from Dr Brooks' own laboratory support this conclusion and also show that this reduction in glucose use is associated with a decrease in the rate of gluconeogenesis. These recent observations confirm prior studies of moderate-intensity exercise. 4. Based on the above, it is clear that the crossover concept cannot be considered an important new concept in exercise metabolism. Instead, the crossover concept actually serves to hinder understanding in this area.